Relationship Between Cognitive and Clinical Insight at Different Durations of Untreated Attenuated Psychotic Symptoms in High-Risk Individuals - Xu, LiHua; Zhang, Mei; Wang, ShuQin; Wei, YanYan; Cui, HuiRu; Qian, ZhenYing; Wang, YingChan; Tang, XiaoChen; Hu, YeGang; Tang, YingYing; Zhang, TianHong; Wang, JiJun (Frontiers in Psychiatry, 2021)
Background: This study examines whether cognitive insight is impaired in high-risk individuals with attenuated psychotic symptoms (APS) and explores the relationship between cognitive and clinical insight at different durations of untreated attenuated psychotic symptoms (DUAPS). Methods: The Structured Interview for Psychosis high-risk Syndrome (SIPS) was used to identify APS individuals. APS (n=121) and healthy control (HC, n=87) subjects were asked to complete the Beck Cognitive Insight Scale (BCIS). Clinical insight of APS individuals was evaluated using the Schedule for Assessment of Insight (SAI). APS individuals were classified into four subgroups based on DUAPS, including 0–3, 4–6, 7–12, and >12 months. Power analysis for significant correlation was conducted using the WebPower package in R. Results: Compared with HC subjects, APS individuals showed poorer cognitive insight, with lower scores on BCIS self-reflectiveness and composite index (BCIS self-reflectiveness minus BCIS self-certainty). Only when DUAPS was longer than 12 months did the significant positive correlation between cognitive and clinical insight obtain the power about 0.8, including the associations between self-reflectiveness and awareness of illness, self-reflectiveness and the total clinical insight, and composite index and awareness of illness. The positive associations of composite index with awareness of illness within 0-3 months DUAPS and with the total score of SAI when DUAPS >12 months were significant but failed to obtain satisfactory power. Conclusions: APS individuals may have impaired cognitive insight, demonstrating lower self-reflectiveness. The correlation between cognitive and clinical insight is associated with the duration of untreated attenuated psychotic symptoms.